Electrode material, method for manufacturing electrode material, and method for manufacturing all-solid-state battery
By coating composite particles with fluoride solid electrolyte in a wet process with controlled solvent addition, the method addresses the issue of sulfide electrolyte deterioration, stabilizing the electrode and reducing resistance in all-solid-state batteries.
Patent Information
- Application Number
- JP2022110387
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-07-08
- Publication Date
- 2025-01-22
- Estimated Expiration
- 2042-07-08
AI Technical Summary
Sulfide solid electrolytes used in all-solid-state batteries face rapid deterioration due to direct contact with active materials, leading to increased resistance, which is exacerbated by inadequate interface formation during coating processes, whether dry or wet.
A method involving composite particles coated with a fluoride solid electrolyte, which forms a stable interface with sulfide solid electrolyte using a wet process, maintaining a high solid content concentration and alternating kneading with solvent addition to ensure dense coating, thereby reducing resistance increase over durability.
The method stabilizes the electrode material, promoting a dense coating of sulfide solid electrolyte, resulting in reduced resistance increase during durability tests, enhancing the performance of all-solid-state batteries.
Smart Images

Figure 0007619984000003 
Figure 0007619984000004 
Figure 0007619984000005
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an electrode material, a method for producing an electrode material, and a method for producing an all-solid-state battery. [Background technology]
[0002] Japanese Patent Laid-Open Publication No. 2014-154407 (Patent Document 1) discloses coating the surfaces of composite particles with a sulfide solid electrolyte. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2014-154407 A Summary of the Invention [Problem to be solved by the invention]
[0004] Hereinafter, solid electrolyte may be abbreviated as "SE." For example, sulfide solid electrolyte may be abbreviated as "sulfide SE."
[0005] Sulfide SE has both high ionic conductivity and excellent moldability. Sulfide SE is suitable for bulk-type all-solid-state batteries. However, direct contact of sulfide SE with active materials in electrodes can accelerate degradation of sulfide SE. Degradation of sulfide SE can result in, for example, loss of ionic conductivity.
[0006] To reduce direct contact between the sulfide SE and the active material, it has been proposed to form composite particles by coating the active material with an oxide SE (e.g., LiNbO3, etc.). It has also been proposed to coat the composite particles with sulfide SE to promote interface formation between the composite particles and the sulfide SE.
[0007] There are two methods for coating composite particles with sulfide SE: a dry method and a wet method. In the dry method, a large mechanical load is applied to the surface of the composite particles. This may cause the oxide SE to peel off. The peeling of the oxide SE may cause direct contact between the active material and the sulfide SE. As a result, the resistance increase rate after durability testing may be high.
[0008] In the wet method, the presence of a solvent (liquid) can reduce the mechanical load applied to the surface of the composite particles. However, in the wet method, the interface formation between the oxide SE and the sulfide SE tends to be difficult to proceed. Since the interface formation is insufficient, the resistance increase rate after durability testing may be high.
[0009] An object of the present disclosure is to reduce the rate of increase in resistance after durability testing. [Means for solving the problem]
[0010] The technical configuration and effects of the present disclosure will be described below. However, the mechanism of action in this specification includes assumptions. The mechanism of action does not limit the technical scope of the present disclosure.
[0011] 1. The electrode material has a solid content of 72% or more. The electrode material includes composite particles, a sulfide solid electrolyte, and a solvent. The composite particles include an active material and a fluoride solid electrolyte. The fluoride solid electrolyte covers at least a portion of the surface of the active material. The sulfide solid electrolyte is attached to the composite particles.
[0012] The electrode material described in "1" above includes a solvent. That is, the electrode material can be produced by a wet method. The surface of the composite particle is coated with a fluoride SE. According to the new findings of the present disclosure, the interface between the fluoride SE and the sulfide SE can be formed relatively easily even by a wet method. Furthermore, in the wet method, the fluoride SE is less likely to peel off.
[0013] The solid content concentration of the electrode material is 72% or more. Due to this, the electrode material tends to be easily and stably kneaded. By performing stable kneading, the surface of the composite particles can be densely coated with the sulfide SE. Due to the synergistic effect of these actions, a reduction in the resistance increase rate after durability is expected.
[0014] 2. In the electrode material described in the above "1", the fluoride solid electrolyte may be represented by, for example, the following formula (1). Li 6-nx M x F6…(1) In the above formula (1), x satisfies 0 < x < 2. M is at least one selected from the group consisting of a semi-metal atom and a metal atom excluding Li. n indicates the oxidation number of M.
[0015] The fluoride SE of the above formula (1) may be relatively easy to form an interface with the sulfide SE. Furthermore, it is expected that the increase in reaction resistance of the fluoride SE is moderate during durability.
[0016] 3. In the electrode material described in the above "2", M in the above formula (1) may include, for example, an atom having an oxidation number of +4.
[0017] 4. In the electrode material described in the above "2", M in the above formula (1) may include, for example, an atom having an oxidation number of +3.
[0018] 5. In the electrode material described in the above "2", M in the above formula (1) may include at least one selected from the group consisting of, for example, Ca, Mg, Al, Y, Ti, and Zr.
[0019] 6. The electrode material described in any one of the above "1" to "5" may have, for example, a solid content concentration of 75.5 to 82%.
[0020] Due to the solid content concentration being 75.5 to 82%, a reduction in the resistance increase rate is expected. This is presumably because kneading is likely to be stable.
[0021] 7. A method for producing an electrode material includes the following (a) and (b): (a) Prepare a composite particle. (b) Producing an electrode material comprising the composite particles, a sulfide solid electrolyte, and a solvent. The composite particles include an active material and a fluoride solid electrolyte. The fluoride solid electrolyte covers at least a part of the surface of the active material. The electrode material has a solid content of 72% or more. The above (b) includes the following (b1) and (b2). (b1) A mixture containing the composite particles, the sulfide solid electrolyte, and a solvent is kneaded. (b2) Adding a solvent to the mixture. The above (b1) and (b2) are each carried out alternately two or more times.
[0022] By kneading a mixture containing the composite particles, sulfide SE, and a solvent, the surfaces of the composite particles can be coated with sulfide SE. During kneading, the solvent may run out due to partial evaporation or absorption by the powder. If the solvent is insufficient, the kneading cannot be maintained and dispersion may be insufficient. In the manufacturing method described in "7" above, kneading and the addition of solvent are alternately repeated. This allows the kneading to be continued without a shortage of solvent. As a result, it is expected that the surfaces of the composite particles will be densely coated with sulfide SE.
[0023] In kneading, the final amount (total amount) of solvent added to the mixture is the amount that takes into account the amount absorbed by the powder and the amount that volatilizes during mixing. If the solvent is not added in multiple portions and the final amount is added all at once, the mixture may liquefy. In particular, in the case of composite particles (powders) containing fluoride SE, the absorption of the solvent into the powder tends to be slow. Therefore, powders containing fluoride SE have a significant tendency to liquefy. If the mixture liquefies, kneading cannot be continued and the desired coating process may not be completed.
[0024] 8. A method for producing an all-solid-state battery includes the following (c) and (d): (c) An electrode containing the electrode material according to any one of the above items "1" to "6" is produced. (d) Fabricating an all-solid-state battery including the electrodes.
[0025] The manufacturing method described in "8" above is expected to produce an all-solid-state battery with a low resistance increase rate during durability.
[0026] Hereinafter, an embodiment of the present disclosure (hereinafter may be abbreviated as "the present embodiment") and an example of the present disclosure (hereinafter may be abbreviated as "the present embodiment") will be described. However, the present embodiment and the present embodiment do not limit the technical scope of the present disclosure. The present embodiment and the present embodiment are illustrative in all respects. The present embodiment and the present embodiment are non-restrictive. The technical scope of the present disclosure encompasses all modifications within the meaning and scope equivalent to the description of the claims. For example, it is originally intended that any configuration may be extracted from the present embodiment and the present embodiment, and that they may be arbitrarily combined. [Brief description of the drawings]
[0027] [Figure 1] FIG. 1 is a schematic flow chart of the manufacturing method according to the present embodiment. [Diagram 2] FIG. 2 is a conceptual diagram showing the progress of kneading. [Diagram 3] FIG. 3 is a conceptual diagram of the all-solid-state battery in this embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0028] <Terms and definitions> The words "comprise," "include," "have," and variations thereof (e.g., "consisting of") are open-ended. The open-ended form may or may not include additional elements in addition to the required elements. The words "consisting of" are closed-ended. However, the closed form does not exclude additional elements that are normally associated with the technology or that are unrelated to the technology disclosed. The words "consisting essentially of..." are semi-closed. The semi-closed form allows for the addition of elements that do not substantially affect the basic and novel characteristics of the technology disclosed.
[0029] "At least one of A and B" includes "A or B" as well as "A and B." "At least one of A and B" can also be written as "A and / or B."
[0030] Expressions such as "may" and "may" are used in the permissive sense, meaning "to have the possibility," rather than in the obligatory sense, meaning "to have to."
[0031] Elements expressed in the singular form include the plural form unless otherwise specified. For example, a "particle" can mean not only "one particle" but also "an aggregate of particles (powder, powder, particle group)."
[0032] Unless otherwise specified, the order of execution of multiple steps, operations, and the like included in various methods is not limited to the order described. For example, multiple steps may proceed simultaneously. For example, multiple steps may be performed in sequence.
[0033] For example, a numerical range such as "m to n%" includes an upper limit and a lower limit. That is, "m to n%" indicates a numerical range of "m% or more and n% or less." Furthermore, "m% or more and n% or less" includes "more than m% and less than n%." Furthermore, a numerical value arbitrarily selected from within the numerical range may be set as a new upper limit or lower limit. For example, a new numerical range may be set by arbitrarily combining a numerical value within the numerical range with a numerical value described in another part of this specification, in a table, in a figure, or the like.
[0034] All numerical values are modified by the term "about." The term "about" may mean, for example, ±5%, ±3%, ±1%, etc. All numerical values may be approximations that may vary depending on the application of the disclosed technology. All numerical values may be expressed with significant figures. Measurements may be average values of multiple measurements. The number of measurements may be three or more, five or more, or ten or more. In general, the more measurements are taken, the more reliable the average value is expected to be. Measurements may be rounded off based on the number of significant figures. Measurements may include errors associated with, for example, the detection limits of the measuring device.
[0035] When a compound is expressed by a stoichiometric composition formula (e.g., "LiCoO2", etc.), the stoichiometric composition formula is merely a representative example of the compound. The compound may have a non-stoichiometric composition. For example, when lithium cobalt oxide is expressed as "LiCoO2", unless otherwise specified, the lithium cobalt oxide is not limited to the composition ratio of "Li / Co / O=1 / 1 / 2" and may contain Li, Co, and O in any composition ratio. Furthermore, doping, substitution, etc. with trace elements may also be allowed.
[0036] "Semi-metals" include B, Si, Ge, As, Sb, and Te. "Metals" refers to elements from Groups 1 to 16 of the periodic table, other than "H, B, Si, Ge, As, Sb, Te, C, N, P, O, S, and Se." When an inorganic compound contains at least one of a semi-metal and a metal and F, the semi-metal and the metal may have a positive (+) oxidation number.
[0037] "Electrode" is a general term for a positive electrode or a negative electrode. The electrode may be a positive electrode or a negative electrode.
[0038] The "thickness of the coating" by the fluoride SE can be measured by the following procedure. A sample is prepared by embedding the composite particles in a resin material. The sample is subjected to a cross-section processing by an ion milling device. For example, a product named "Arblade (registered trademark) 5000" (or an equivalent product) manufactured by Hitachi High-Technologies Corporation may be used. The cross-section of the sample is observed by a SEM (Scanning Electron Microscope). For example, a product named "SU8030" (or an equivalent product) manufactured by Hitachi High-Technologies Corporation may be used. The thickness of the fluoride SE is measured in 20 fields of view for each of 10 composite particles. The arithmetic average of the thicknesses at 200 points in total is regarded as the thickness of the coating. The thickness of the coating by the fluoride SE may also be referred to as the "thickness of the buffer layer".
[0039] The thickness of the coating may be measured in an element mapping image by SEM-EDX (Energy Dispersive X-ray Spectrometry). In the element mapping image, an element representative of each part is selected. As an example, Ni may be selected as a representative element of the active material, and F may be selected as a representative element of the fluoride SE.
[0040] The "coverage rate" is measured by the following procedure. A cross-sectional sample of the composite particle is prepared in the same manner as the sample for measuring the coating thickness. In the cross-sectional SEM image, the length (L0) of the contour of the active material is measured. The length (L1) of the portion of the contour of the active material (core particle) that is covered with fluoride SE is measured. The coverage rate is the percentage of L1 divided by L0. The coverage rate is measured for each of 20 composite particles. The arithmetic average of the 20 coverage rates is considered to be the "coverage rate."
[0041] For example, L0 and L1 may be calculated by performing image processing on an element mapping image obtained by SEM-EDX.
[0042] A "hollow particle" refers to a particle in which the area of the cavity in the center is 30% or more of the cross-sectional area of the entire particle in a cross-sectional image of the particle (e.g., a cross-sectional SEM image, etc.). A "solid particle" refers to a particle in which the area of the cavity in the center is less than 30% of the cross-sectional area of the entire particle in a cross-sectional image of the particle.
[0043] "D50" refers to the particle size at which the cumulative frequency of the smaller particle sizes reaches 50% in a volume-based particle size distribution. D50 can be measured using a laser diffraction particle size distribution analyzer.
[0044] The "average Feret diameter" is measured on a two-dimensional image of a particle. The arithmetic mean of the maximum Feret diameters of 20 or more particles is the "average Feret diameter".
[0045] "Solid content concentration" refers to the ratio of the total mass of the components other than the solvent to the total mass of the mixture. The solid content concentration is expressed as a percentage.
[0046] A "solvent" refers to a liquid material that has the ability to dissolve some solute. The type of solute can be arbitrary. The solute does not necessarily have to actually be dissolved in the solvent. A liquid material that has the ability to dissolve a solute is also called a "solvent" when it is used for purposes other than dissolving the solute.
[0047] <Electrode material> The electrode material is in a wet state. The electrode material may be, for example, granular, powdery, clayey, or the like. The electrode material is a raw material for an electrode. For example, a slurry containing the electrode material may be formed. The electrode can be manufactured by applying the slurry to a surface of a substrate. The electrode material includes composite particles, a sulfide SE, and a solvent.
[0048] 《Composite particles》 The composite particles include an active material and a fluoride SE. The composite particles may have a D50 of, for example, 1 to 30 μm, 3 to 20 μm, or 5 to 15 μm. The composite particles may have any shape. The composite particles may be, for example, spherical, ellipsoidal, flaky, fibrous, or the like.
[0049] (Fluoride solid electrolyte) The fluoride SE is the shell of the composite particles. The fluoride SE is interposed between the active material and the sulfide SE. The SE inserted between the active material and the sulfide SE is also referred to as a "buffer layer". The fluoride SE can promote the formation of an interface with the sulfide SE even in the coexistence of a solvent. The fluoride SE covers at least a part of the surface of the active material. The thickness of the coating may be, for example, 1 to 100 nm or 1 to 50 nm. The compounding amount of the fluoride SE may be, for example, 1 to 10 parts by mass or 2 to 3 parts by mass with respect to 100 parts by mass of the active material.
[0050] The fluoride SE may cover all of the surface of the active material or may cover a part of the surface. The fluoride SE may be distributed in an island shape on the surface of the active material. The coverage rate may be, for example, 50 to 100%, 60 to 100%, 70 to 100%, 80 to 100%, or 90 to 100%. The higher the coverage rate, for example, the lower reduction of the initial resistance is expected.
[0051] The fluoride SE can have any composition as long as it contains F. The fluoride SE may contain, for example, Li and F.
[0052] The fluoride SE may be represented, for example, by the following formula (1). Li 6-nx M x F6…(1) In the above formula (1), x satisfies 0 < x < 2. M is at least one selected from the group consisting of a semi-metal atom and a metal atom other than Li. n indicates the oxidation number of M.
[0053] In the above formula (1), M may be composed of a single atom or may be composed of multiple types of atoms. When M is composed of multiple types of atoms, n represents the weighted average of the oxidation numbers of each atom. For example, when M contains Ti (oxidation number = +4) and Al (oxidation number = +3), the molar ratio of Ti to Al is "Ti / Al = 3 / 7", and x = 1, n is 3.3 according to the formula "n = 0.3 x 4 + 0.7 x 3".
[0054] In the above formula (1), x may satisfy, for example, 0.1≦x≦1.9, 0.2≦x≦1.8, 0.3≦x≦1.7, 0.4≦x≦1.6, 0.5≦x≦1.5, 0.6≦x≦1.4, 0.7≦x≦1.3, 0.8≦x≦1.2, or 0.9≦x≦1.1.
[0055] M may, for example, include an atom having an oxidation number of +4. M may, for example, include an atom having an oxidation number of +3. M may, for example, include an atom having an oxidation number of +4 and an atom having an oxidation number of +3.
[0056] In the above formula (1), M may, for example, include at least one selected from the group consisting of Ca, Mg, Al, Y, Ti, and Zr. M may, for example, include at least one selected from the group consisting of Al, Y, and Ti. M may, for example, include at least one selected from the group consisting of Al and Ti.
[0057] The fluoride SE may be represented, for example, by the following formula (2): Li 3-x Ti x Al 1-x F6…(2) In the above formula (2), x may satisfy, for example, 0≦x≦1, 0.1≦x≦0.9, 0.2≦x≦0.8, 0.3≦x≦0.7, or 0.4≦x≦0.6.
[0058] (active material) The active material is a core of a composite particle. The active material is particulate. The active material may be, for example, a secondary particle. The secondary particle is an aggregate of primary particles. The D50 of the secondary particle may be, for example, 1 to 30 μm, 3 to 20 μm, or 5 to 15 μm. The average Feret diameter of the primary particles may be, for example, 0.01 to 3 μm.
[0059] The active material may have any shape. For example, the active material may be spherical, ellipsoidal, flaky, fibrous, etc. The active material may be solid or hollow particles.
[0060] The active material may be, for example, a positive electrode active material. The positive electrode active material can cause a positive electrode reaction. The positive electrode active material may contain any component. The positive electrode active material may contain, for example, at least one selected from the group consisting of LiCoO2, LiNiO2, LiMnO2, LiMn2O4, Li(NiCoMn)O2, Li(NiCoAl)O2, Li(NiCoMnAl)O2, and LiFePO4. For example, "(NiCoMn)" in "Li(NiCoMn)O2" indicates that the sum of the composition ratios in parentheses is 1. As long as the sum is 1, the amount of each component is arbitrary. Li(NiCoMn)O2 is, for example, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiNi 0.4 Co 0.3 Mn 0.3 O2, LiNi 0.5 Co 0.2 Mn 0.3 O2, LiNi 0.5 Co 0.3 Mn 0.2 O2, LiNi 0.5 Co 0.4 Mn 0.1 O2, LiNi 0.5 Co 0.1 Mn 0.4 O2, LiNi 0.6 Co 0.2 Mn 0.2 O 2、 LiNi 0.6 Co 0.3 Mn 0.1 O 2、LiNi 0.6 Co 0.1 Mn 0.3 O 2、 LiNi 0.7 Co 0.1 Mn 0.2 O 2、 LiNi 0.7 Co 0.2 Mn 0.1 O 2、 LiNi 0.8 Co 0.1 Mn 0.1 O 2、 and LiNi 0.9 Co 0.05 Mn 0.05 Li(NiCoAl)O2 may contain at least one selected from the group consisting of LiNi 0.8 Co 0.15 Al 0.05 It may contain O2 etc.
[0061] The positive electrode active material may be represented, for example, by the following formula (3). Li 1-y Ni x M 1-x O2…(3) 0.5≦x≦1 -0.5≦y≦0.5 In the above formula (3), M may include at least one selected from the group consisting of Co, Mn, and Al, and x may be, for example, 0.6 or more, 0.7 or more, 0.8 or more, or 0.9 or more.
[0062] The positive electrode active material may contain additives, for example. The additives may be, for example, substitutional solid solution atoms, interstitial solid solution atoms, etc. The additives may be deposits adhering to the surface of the positive electrode active material (primary particles). The deposits may be, for example, simple substances, oxides, carbides, nitrides, halides, etc. The addition amount may be, for example, 0.01 to 0.1, 0.02 to 0.08, or 0.04 to 0.06. The addition amount indicates the ratio of the amount of the additive to the amount of the positive electrode active material. The additives may contain, for example, at least one selected from the group consisting of B, C, N, halogen, Sc, Ti, V, Cu, Zn, Ga, Ge, Se, Sr, Y, Zr, Nb, Mo, In, Sn, W, and lanthanoids.
[0063] The active material may be, for example, a negative electrode active material. The negative electrode active material can cause a negative electrode reaction. The negative electrode active material may contain any components. The negative electrode active material may be, for example, natural graphite, artificial graphite, soft carbon, hard carbon, Si, SiO x (0 < x < 2), Si-based alloy, Sn, SnO x (0 < x < 2), Li, Li-based alloy, and Li4Ti5O 12 and may contain at least one selected from the group consisting of. SiO x (0 < x < 2) may be doped with, for example, Mg or the like. A composite material may be formed by supporting an alloy-based active material (such as Si, etc.) on a carbon-based active material (such as graphite, etc.).
[0064] 《Sulfide solid electrolyte》 The sulfide SE adheres to the surface of the composite particles together with the solvent. The sulfide SE may cover the surface of the composite particles. The sulfide SE is in particle form. The D50 of the sulfide SE may be, for example, 0.01 to 1 μm, or 0.1 to 0.9 μm. The compounding amount of the sulfide SE may be, for example, 0.1 to 20 parts by mass or 0.5 to 15 parts by mass with respect to 100 parts by mass of the active material.
[0065] The sulfide SE may exhibit high ionic conductivity. The sulfide SE may have any composition as long as it contains S (sulfur). The sulfide SE may contain, for example, Li, P, and S. The sulfide SE may further contain, for example, O, Ge, Si, etc. The sulfide SE may further contain, for example, halogens, etc. The sulfide SE may further contain, for example, I, Br, etc. The sulfide SE may be, for example, a glass ceramic type or an argyrodite type. Sulfides SE include, for example, LiI-LiBr-Li3PS4, Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-Li2O-Li2S-P2S5, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li2S-GeS2-P2S5, Li2S-P2S5, Li4P2S6, Li7P3S 11 and Li3PS4.
[0066] For example, "LiI-LiBr-Li3PS4" refers to a sulfide SE produced by mixing LiI, LiBr, and Li3PS4 in any molar ratio. For example, the sulfide SE may be produced by a mechanochemical method. "Li2S-P2S5" includes Li3PS4. Li3PS4 may be produced, for example, by mixing Li2S and P2S5 in a molar ratio of Li2S / P2S5=75 / 25.
[0067] "solvent" The solvent is a liquid. The solvent can promote adhesion between the composite particles and the sulfide SE during kneading. The solvent can function as a dispersion medium in the slurry. The solvent can contain any component. The solvent may contain at least one selected from the group consisting of aromatic hydrocarbons, esters, alcohols, ketones, and lactams. The solvent may contain at least one selected from the group consisting of tetralin (1,2,3,4-tetrahydronaphthalene, THN), butyl butyrate, heptane, and N-methyl-2-pyrrolidone (NMP).
[0068] Butyl butyrate is expected to be less likely to degrade sulfide SE than, for example, NMP, etc. THN is expected to be less likely to degrade sulfide SE than, for example, butyl butyrate and NMP, etc. By including THN in the solvent, for example, it is expected to reduce initial resistance.
[0069] The solid content concentration of the electrode material is 72% or more. When the solid content concentration is 72% or more, the solvent is easily retained inside the powder, and the kneading tends to be easy to carry out. The solid content concentration may be, for example, 74% or more, 75.5% or more, 76% or more, or 78% or more. When the solid content concentration is 76% or more, the solid and the liquid are not easily separated during mixing, and the kneading tends to be easy to stabilize. The solid content concentration in the kneading may be, for example, 90% or less. When the solid content concentration is 90% or less, the mixture is easily wetted uniformly, and the kneading tends to be easy to stabilize. The solid content concentration may be, for example, 88% or less, 85% or less, 83% or less, or 82% or less. The solid content concentration may be, for example, 75.5 to 82%. Within this range, the dispersion tends to be easily promoted. By promoting the dispersion, for example, a reduction in the resistance increase rate is expected.
[0070] <Method of manufacturing electrode materials> FIG. 1 is a schematic flow chart of the manufacturing method in this embodiment. Hereinafter, the "manufacturing method in this embodiment" may be abbreviated as "this manufacturing method." This manufacturing method includes a "manufacturing method for an electrode material." The manufacturing method for an electrode material includes "(a) preparation of composite particles" and "(b) manufacturing of an electrode material."
[0071] (a) Preparation of composite particles The manufacturing method includes preparing composite particles. The composite particles may be prepared by any method. For example, the composite particles may be formed by a dry mechanochemical method. For example, the composite particles may be formed by mixing an active material and a fluoride SE in a particle composite device. An example of the particle composite device is "Nobilta NOB-MINI" manufactured by Hosokawa Micron Corporation. However, any mixing device, granulating device, etc. may be used as long as the particles can be composited.
[0072] (b) Production of electrode materials The present manufacturing method includes manufacturing an electrode material including composite particles, sulfide SE, and a solvent. The electrode material can be manufactured by kneading. In the present manufacturing method, any kneading device can be used as long as it is capable of kneading. For example, a planetary centrifugal mixer or the like may be used.
[0073] For example, first, the sulfide SE (powder) may be dispersed in a solvent (liquid) to prepare a dispersion liquid. In this manufacturing method, any dispersion device may be used. For example, an ultrasonic homogenizer or the like may be used.
[0074] Next, the composite particles (powder) and the dispersion are fed to a kneading device. The mixture begins to become viscous as it is stirred. For example, the mixture may be stirred at a rotation speed of 50 to 100 rpm for 1 minute to 1 hour. Note that the mixing conditions (rotation speed, mixing time, etc.) may vary depending on, for example, the powder properties, the specifications of the device, etc.
[0075] In this manufacturing method, "(b1) kneading" and "(b2) adding solvent" are each performed alternately two or more times. In (b1), the mixture is kneaded. In (b2), a solvent is added to the mixture. By alternately performing (b1) and (b2), the composite particles can be densely coated with sulfide SE. (b1) and (b2) may each be performed alternately, for example, three or more times, or four or more times. (b1) and (b2) may each be performed alternately, for example, five or less times, four or less times, or three or less times.
[0076] FIG. 2 is a conceptual diagram showing the progress of kneading. The first state 301 is a state before kneading. In the composite particle 10, the fluoride SE (fluoride solid electrolyte 12) covers the active material 11. In the first state 301, the periphery of the composite particle 10 is filled with the solvent 30. The sulfide SE (sulfide solid electrolyte 20) is dispersed in the solvent 30. When the surface of the composite particle 10 is covered with the fluoride SE, absorption of the solvent 30 into the surface of the composite particle 10 tends to be difficult.
[0077] By carrying out "(b1) stiff kneading", the first state 301 transitions to the second state 302. In the second state 302, the surface properties of the composite particle 10 change, and the absorption of the solvent 30 progresses. Furthermore, a part of the solvent 30 may evaporate. As the solvent 30 decreases, the solvent 30 (liquid) is dispersed in a solid. In the second state 302, there is a shortage of the solvent 30 required for stiff kneading.
[0078] By "(b2) Addition of solvent", the second state 302 transitions to the third state 303. In the third state 303, the solvent 30 required for kneading is replenished. After replenishing the solvent 30, "(b1) Kneading" is performed again, and the third state 303 returns to the second state 302. By alternately repeating "(b1) Kneading" and "(b2) Addition of solvent", a dense coating layer (sulfide SE) is gradually formed.
[0079] Due to the densification of the coating layer, the second state 302 and the third state 303 transition to a fourth state 304. That is, the coating process is completed, and the electrode material may be completed.
[0080] It is not necessary for all of the sulfide SE in the system to form a coating layer. A portion of the sulfide SE may not contribute to the formation of the coating layer and may be free from the composite particle 10. The coating layer (sulfide SE) may gradually change into a film-like shape as the kneading proceeds. The final coating layer may be smooth. The final coating layer may have an uneven surface.
[0081] <Manufacturing method for all-solid-state batteries> The manufacturing method may include a "method for manufacturing an all-solid-state battery." The method for manufacturing an all-solid-state battery includes, in addition to "(a) preparation of composite particles" and "(b) manufacture of an electrode material," "(c) manufacture of an electrode," and "(d) manufacture of an all-solid-state battery."
[0082] (c) Manufacture of electrodes The method may include producing an electrode including the electrode material. For example, a slurry including the electrode material may be formed. The slurry may be applied to a surface of a substrate and dried to produce an electrode.
[0083] (slurry) For example, the electrode material, the electronic conductive material, the ion conductive material, the binder, and the solvent may be mixed to form a slurry. For example, the mixture may be subjected to a dispersion treatment using an ultrasonic homogenizer or the like. The solid content of the slurry may be, for example, 50 to 70%.
[0084] The electronic conductive material can form an electronic conductive path in the electrode. The amount of the electronic conductive material is arbitrary. The amount of the electronic conductive material may be, for example, 0.1 to 10 parts by mass with respect to 100 parts by mass of the active material. The electronic conductive material may contain any component. The electronic conductive material may contain, for example, at least one selected from the group consisting of carbon black (CB), vapor grown carbon fiber (VGCF), carbon nanotube (CNT) and graphene flake (GF). The CB may contain, for example, at least one selected from the group consisting of acetylene black (AB), Ketjen Black (registered trademark), and furnace black.
[0085] The ion conductive material can form an ion conductive path in the electrode. The ion conductive material may be particulate. The ion conductive material may have a D50 of, for example, 0.01 to 1 μm, 0.01 to 0.95 μm, or 0.1 to 0.9 μm. The amount of the ion conductive material is arbitrary. The amount of the ion conductive material may be, for example, 1 to 200 parts by volume, 50 to 150 parts by volume, or 50 to 100 parts by volume, relative to 100 parts by volume of the active material. The ion conductive material may contain, for example, a sulfide SE, a fluoride SE, or the like. The sulfide SE and fluoride SE contained in the ion conductive material may be the same type as or different from the sulfide SE and fluoride SE contained in the electrode material.
[0086] The binder can bind solid materials together. The amount of the binder may be, for example, 0.1 to 10 parts by mass with respect to 100 parts by mass of the active material. The binder may contain any component. The binder may contain, for example, at least one selected from the group consisting of polyvinylidene fluoride (PVdF), vinylidene fluoride-hexafluoropropylene copolymer (PVdF-HFP), styrene butadiene rubber (SBR), butadiene rubber (BR), and polytetrafluoroethylene (PTFE).
[0087] (Coating) In the present manufacturing method, any coating device may be used. For example, a die coater, a roll coater, or the like may be used. The slurry may be coated on the surface of the substrate. The substrate may be conductive. The substrate may function as a current collector. The substrate may be, for example, sheet-like or mesh-like. The substrate may have a thickness of, for example, 5 to 50 μm. The substrate may include, for example, a metal foil, a metal mesh, a porous metal body, or the like. The substrate may include, for example, at least one selected from the group consisting of Al, Cu, Ni, Cr, Ti, and Fe. The substrate may include, for example, an Al foil, an Al alloy foil, a Ni foil, a Cu foil, a Cu alloy foil, a Ti foil, a stainless steel foil, or the like. The surface of the metal foil may be covered with a carbon layer. The carbon layer may include, for example, a conductive carbon material (for example, AB, etc.).
[0088] The slurry is dried on the surface of the substrate to form an active material layer. In this manufacturing method, any drying device can be used. For example, a hot plate, a hot air dryer, an infrared dryer, etc. may be used.
[0089] After drying the slurry, the electrode may be subjected to a press process. For example, cold press process may be performed, or hot press process may be performed. In the present manufacturing method, any press device may be used. For example, a roll press device or the like may be used. When hot press process is performed, the press temperature may be adjusted depending on, for example, the type of binder. The press temperature may be, for example, 80 to 180°C. After press process, the active material layer may have a thickness of, for example, 10 to 200 μm. After press process, the active material layer may have a density of, for example, 2 to 4 g / cm. 3 may be also possible.
[0090] (d) Manufacturing of all-solid-state batteries The method may include producing an all-solid-state battery including the electrode.
[0091] FIG. 3 is a conceptual diagram of the all-solid-state battery in this embodiment. For example, a power generating element 150 may be formed. The power generating element 150 may be formed by stacking a positive electrode 110, a separator layer 130, and a negative electrode 120. At least one of the positive electrode 110 and the negative electrode 120 is the electrode obtained above. The separator layer 130 is disposed between the positive electrode 110 and the negative electrode 120. The separator layer 130 may include, for example, an ion conductive material and a binder. The separator layer 130 may be formed, for example, by applying a slurry to the surface of at least one of the positive electrode 110 and the negative electrode 120.
[0092] After the power generating element 150 is formed, the power generating element 150 may be subjected to hot pressing. It is expected that the power generating element 150 will become dense through the hot pressing.
[0093] For example, a lead tab, an external terminal, or the like may be connected to the power generating element 150. The power generating element 150 is housed in an exterior body (not shown). The exterior body may be sealed. By housing the power generating element 150 in the exterior body, the all-solid-state battery 200 can be completed.
[0094] The exterior body may have any shape. For example, the exterior body may be a pouch made of a metal foil laminated film. For example, the exterior body may be a case made of a metal. For example, the exterior body may contain Al or the like. The exterior body may house a single power generating element 150 alone, or may house a plurality of power generating elements 150. The plurality of power generating elements 150 may form a series circuit or a parallel circuit. EXAMPLES
[0095] <Experiment 1> In Experiment 1, composite particles were investigated. The electrode materials and all-solid-state batteries according to the following Nos. 1-1 to 1-4 were manufactured. Hereinafter, for example, "electrode material according to No. 1-1" may be abbreviated as "No. 1-1".
[0096] No.1-1 Li(NiCoAl)O2 was prepared as the active material. Hereinafter, "Li(NiCoAl)O2" may be abbreviated as "NCA."
[0097] Fluoride SE was synthesized by mixing LiF, TiF4, and AlF3 in a planetary ball mill. 2.7 Ti 0.3 Al 0.7 The composition of the compound was F6. 2.7 Ti 0.3 Al 0.7 "F6" may be abbreviated as "LTAF."
[0098] A "Nobilta NOB-MINI (manufactured by Hosokawa Micron Corporation)" was prepared as a particle compositing device. In the particle compositing device, 48.7 parts by mass of NCA and 1.3 parts by mass of LTAF were subjected to a compositing process to form composite particles. The operating conditions of the device were as follows:
[0099] Power: 12W per gram of material Rotational speed: 6000 rpm Processing time: 30 minutes
[0100] The following materials were prepared: Sulfide SE: Li2S-P2S5 (glass ceramics) Solvent:THN Hereinafter, "Li2S-P2S5" may be abbreviated as "LPS."
[0101] The subsequent operations were carried out in an environment where the dew point temperature was controlled to -70°C or less. An ultrasonic homogenizer was prepared as a dispersion device. 98.4 parts by mass of sulfide SE was dispersed in 229.6 parts by mass of solvent by the ultrasonic homogenizer to prepare a dispersion liquid.
[0102] A planetary mixer was prepared as a kneading device. 1000 parts by mass of the composite particles were supplied to the kneading device. Furthermore, the dispersion liquid obtained above was supplied to the kneading device.
[0103] The electrode material was produced by alternately repeating "kneading" and "adding solvent" in the following order: In the electrode material, the composite particles were coated with sulfide SE.
[0104] (1) Stiff kneading: Rotation speed = 70 rpm, Time = 10 minutes (2) Addition of solvent: THN (34 parts by weight) (3) Stiff kneading: Rotation speed = 100 rpm, Time = 10 minutes (4) Addition of solvent: THN (37 parts by mass) (5) Thick kneading: Rotation speed = 100 rpm, Time = 10 minutes (6) Addition of solvent: THN (23 parts by weight) (7) Thick kneading: Rotation speed = 100 rpm, Time = 4 hours
[0105] A slurry was prepared by dispersing the electrode material, ion conductive material (LPS), and electronic conductive material (AB+VGCF) in a solvent (THN) using an ultrasonic homogenizer. The slurry was applied to the surface of the substrate and dried to produce a positive electrode. Furthermore, an all-solid-state battery including the positive electrode was manufactured. The structure of the all-solid-state battery is as follows:
[0106] Exterior: Aluminum laminated film Negative electrode active material: Li4Ti5O 12
[0107] No.1-2 A slurry was prepared by dispersing the composite particles of No. 1-1, the ion conductive material, and the electron conductive material in a solvent using an ultrasonic homogenizer. A positive electrode and an all-solid-state battery were manufactured in the same manner as in No. 1-1, except for this. In No. 1-2, the composite particles were not kneaded (coated with sulfide SE).
[0108] No.1-3 A precursor solution was prepared by mixing ethoxylithium, pentaethoxyniobium, and ultra-dehydrated ethanol. The surface of NCA was coated with the precursor solution to form composite particles. The composite particles were then heat-treated to produce oxide SE. The oxide SE had the composition LiNbO3.
[0109] A dispersion liquid was prepared by dispersing 98.4 parts by mass of sulfide SE in 229.6 parts by mass of solvent using an ultrasonic homogenizer. 1000 parts by mass of composite particles were supplied to a kneading device. The dispersion liquid obtained above was further supplied to the kneading device.
[0110] 69 mass of the solvent was supplied to the kneading device. Kneading was carried out for 4 hours at a rotation speed of 100 rpm. Except for these, a positive electrode and an all-solid-state battery were manufactured in the same manner as in No. 1-1.
[0111] No.1-4 A positive electrode and an all-solid-state battery were manufactured in the same manner as in No. 1-3, except that the composite particles were not subjected to kneading (coating treatment with sulfide SE).
[0112] No.1-5 The same operation as in No. 1-1 was carried out until 1000 parts by mass of the composite particles and the dispersion liquid were supplied to the kneading device.
[0113] 94 parts by weight of solvent were added to the mixture. 94 parts by weight corresponds to the final amount (total amount) of solvent in No. 1-1. After the addition of the solvent, the first kneading (rotation speed = 70 rpm, time = 10 min) was performed. Then, the second kneading (rotation speed = 100 rpm, time = 10 min) was performed. During the second kneading, the mixture liquefied. Therefore, the coating treatment with sulfide SE was not completed. In No. 1-5, the solvent was not added in portions, but the entire amount was added at once.
[0114] "evaluation" The SOC (State Of Charge) of the solid-state battery was adjusted to 50%. The solid-state battery was discharged for 10 seconds at an hourly rate of 60.2C. The initial discharge resistance (DC resistance) was calculated from the voltage drop and current during discharge. The discharge resistance was calculated at 0.1 seconds, 2 seconds, and 10 seconds after the start of discharge.
[0115] Furthermore, the solid-state battery was charged for 5 seconds at a time rate of 60.2 C. The initial charging resistance (DC resistance) was calculated from the voltage rise and current during charging. The charging resistance was calculated at 0.1 seconds, 1 second, and 5 seconds after the start of charging.
[0116] After measuring the initial discharge resistance and the initial charge resistance, a durability test was carried out, that is, a pulse charge / discharge cycle was carried out under the following conditions.
[0117] Test temperature: 80℃ SOC range: 50~60% Charge / discharge cycle count: 800
[0118] After the durability test, the discharge resistance and charge resistance after durability were measured in the same manner as before durability (initial period). The resistance increase rate was calculated by dividing the resistance after durability by the resistance before durability.
[0119] [Table 1]
[0120] In Table 1 above, there is a tendency for the resistance increase rate to decrease by covering the composite particles with sulfide SE (comparison between No. 1-1 and 1-2, and comparison between No. 1-3 and 1-4).
[0121] In Table 1, the fluoride SE tends to have a lower resistance increase rate than the oxide SE (comparison between No. 1-1 and 1-3). This is thought to be because the interface between the fluoride SE and the sulfide SE is relatively easy to form.
[0122] <Experiment 2> In Experiment 2, the solid content concentration of the electrode material was examined. Electrode materials and all-solid-state batteries according to No. 2-1 to 2-7 in Table 2 below were manufactured. Each electrode material has a different solid content concentration. No. 2-1 has the same specifications as No. 1-2 in Experiment 1. No. 2-2 to 2-7 have the same specifications as No. 1-1 in Experiment 1, except for the solid content concentration.
[0123] "evaluation" The resistance increase rate was measured in the same manner as in Experiment 1. Table 1 below shows the increase rate of discharge resistance 2 seconds after the start of discharging and the increase rate of charge resistance 5 seconds after the start of charging.
[0124] [Table 2]
[0125] When the solid content was 74%, the solid and liquid began to separate one hour after the start of kneading (No. 2-2). Therefore, it was difficult to knead for more than one hour.
[0126] When the solid content was 75.5%, the solid and liquid began to separate 3 hours after the start of kneading (No. 2-3). Therefore, it was difficult to knead for more than 3 hours.
[0127] When the solid content was in the range of 78 to 85%, stable kneading was possible for 4 hours or more (Nos. 2-4 to 2-7).
[0128] When the solid content is in the range of 75.5 to 82%, the resistance increase rate tends to be low. This is probably because dispersion can be promoted during thick kneading (Nos. 2-3 to 2-6). [Explanation of symbols]
[0129] 10 composite particle, 11 active material, 12 fluoride solid electrolyte, 20 sulfide solid electrolyte, 30 solvent, 110 positive electrode, 120 negative electrode, 130 separator layer, 150 power generating element, 200 all-solid-state battery, 301 first state, 302 second state, 303 third state, 304 fourth state.
Claims
1. Having a solids concentration of 75.5 to 82%, Composite particles, a sulfide solid electrolyte, and a solvent, the composite particles include an active material and a fluoride solid electrolyte, the fluoride solid electrolyte covers at least a part of a surface of the active material, The sulfide solid electrolyte is attached to the composite particles. electrode material.
2. The fluoride solid electrolyte has the formula (1): <h2 style=";text-align:left;direction:ltr">Li<h2 style=";text-align:left;direction:ltr"> 6-nx <h2 style=";text-align:left;direction:ltr"> 8<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> F<h2 style=";text-align:left;direction:ltr"> 6 <h2 style=";text-align:left;direction:ltr"> …(1) is represented by In the formula (1), x satisfies 0<x<2, M is at least one selected from the group consisting of metalloid atoms and metal atoms other than Li; n indicates the oxidation number of M; The electrode material according to claim 1 .
3. In the formula (1), M contains an atom having an oxidation number of +4; The electrode material according to claim 2 .
4. In the formula (1), M contains an atom having an oxidation number of +3; The electrode material according to claim 2 .
5. In the formula (1), M includes at least one selected from the group consisting of Ca, Mg, Al, Y, Ti, and Zr; The electrode material according to claim 2 .
6. The solvent comprises tetralin. The electrode material according to any one of claims 1 to 5.
7. (a) providing a composite particle; and (b) producing an electrode material comprising the composite particles, a sulfide solid electrolyte, and a solvent; Including, the composite particles include an active material and a fluoride solid electrolyte, the fluoride solid electrolyte covers at least a part of a surface of the active material, The electrode material has a solids concentration of 75.5 to 82%; The (b) is (b1) kneading a mixture containing the composite particles, the sulfide solid electrolyte, and the solvent; and (b2) adding the solvent to the mixture; Including, The (b1) and the (b2) are alternately performed two or more times each; A method for producing an electrode material.
8. (c) producing an electrode comprising the electrode material according to any one of claims 1 to 5; and (d) fabricating an all-solid-state battery comprising the electrode; Including, How solid-state batteries are manufactured.
Citation Information
Patent Citations
All-solid type secondary battery
JP2013008611A
Composite active material and manufacturing method thereof
JP2014154407A
Positive electrode material, and battery
WO2021187391A1